PRESERVING LOCAL WISDOM THROUGH TRANSLATION: A STUDY OF CULTURAL TERM PROCEDURES IN ACEHNESE PEUSIJUEK RITUALS - Rahmah Sarita; Zainuddin Hasibuan; Susi Asmara; Ainul Susan; Nazriel Anhar (Merwin Publisher, 2026)
The translation of culture terms poses significant challenges because such terms embody cultural values, beliefs, and concepts that often lack direct lexical equivalents in the target language. Although previous studies have examined the cultural values embedded in the Peusijuek tradition, limited attention has been given to the translation procedures used to render its culture-bound terms into English. Therefore, this study aims to identify the categories of culture-bound terms found in the Peusijuek tradition and analyze the translation procedures employed in rendering them into English. A qualitative descriptive approach was adopted because it enables an in-depth analysis of translation procedures and their roles in preserving cultural meaning. The data were collected from Language and Cultural Values in the Peusijuek Tradition of Acehnese Society: An Anthropolinguistic Study by Salman, Irana, and Suri (2025). Cultural terms were first categorized based on Newmark's (1988) classification and subsequently analyzed using Pinchuck's (1977) translation procedures. A total of 32 occurrences (N = 32) of translation procedures were identified. The findings reveal that literal translation is the most frequently applied procedure (46.9%), followed by borrowing (25.0%), modulation (25.0%), and transposition (3.1%). The predominance of literal translation suggests that many cultural terms in the Peusijuek tradition can be translated directly without substantially altering their conceptual meanings, while borrowing is employed to preserve culture-specific terms that have no direct lexical equivalents in English. These findings highlight the importance of selecting appropriate translation procedures to balance semantic accuracy with cultural preservation. This study contributes to translation studies by providing empirical evidence of how translation procedures facilitate the transfer of culture-bound meanings while maintaining the authenticity of Acehnese cultural expressions, thereby supporting intercultural communication and the preservation of local cultural heritage.